Evaluation of provider documentation of medication management in a Patient-Centered Medical Home (PCMH) - Trang T. Nguyen; Bella H. Mehta; Jennifer L. Rodis; Kristin A Casper; Randell K. Wexler (University of Minnesota Libraries Publishing, 2014)
Purpose: The National Committee for Quality Assurance (NCQA) has standards for recognizing Patient-Centered Medical Homes (PCMH) including one for medication management. Study objectives were to identify if and how providers within a PCMH recognized under the 2008 guidelines were documenting components of medication management to meet NCQA's 2011 requirements including: 1) providing information about new prescriptions to >80% of patients; 2) assessing understanding of medications for >50% of patients; and 3) assessing response and barriers to medication adherence for >50% of patients. Methods: Physician and pharmacist-led patient visits from a family medicine office, from February 1 to August 1, 2012 were assessed. Patients over 18 years old taking at least one medication were included. A retrospective chart review was performed to assess documented components of medication management. Descriptive statistics were used to analyze data. Results: A systematic sampling of 450 physician-led and 195 pharmacist-led patient visits, demonstrated providers did not meet documentation goals for providing patients information on new prescriptions (65% pharmacist, 24% physician, 36% of total provider notes) or for assessment of patients' understanding of medications (9% pharmacist 12% physician, 11% of total provider notes). Individually each type of provider did not meet the goal of assessing patient response and barriers to adherence to medication, but with combined intervention by the pharmacists and the physicians, the site was able to surpass NCQA's percentage goal (57% and 58%). Conclusions: No components of medication management are well documented. Using the electronic medical record, pharmacists may be able to develop documentation tools and assist sites to meet NCQA's goals for medication management.   Type: Original Research